Strengthening the Climate Information Architecture - Ferreira, Caio.; Rozumek, David; Singh, Ranjit; Suntheim, Felix (Washington, D.C. : International Monetary Fund, 2021)
Strengthening the climate information architecture is paramount to promote transparency and global comparability of data and thus improve market confidence, safeguard financial stability, and foster sustainable finance. This note provides a conceptual framework around the provision of climate-related information, discusses the progress made to date, and points toward the way forward. Progress and convergence are required on the three buildings blocks of a climate information architecture: (1) high-quality, reliable, and comparable data; (2) a globally harmonized and consistent set of climate disclosure standards; and (3) a globally agreed upon set of principles for climate finance taxonomies. A decisive, globally coordinated effort is needed to move forward on all three fronts.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: Climate; Environmental Economics; General Financial Markets; Global Warming; Natural Disasters and Their Management